Study of the Hejő brook watershed fish fauna - Harka, Ákos; Szepesi, Zsolt (Acta Agraria Debreceniensis, 2007)
Literature sources mention 18 fish species from the Hejő watershed. In order to learn more about the fauna, we studied the brook and its tributaries between 2003–2005. We detected a total of 32 fishspecies, 17 of which are new for the watershed. Most of these are native species (Rutilus rutilus, Leuciscus leuciscus, Leuciscus idus, Aspius aspius, Leucaspius delineatus, Gobio albipinnatus, Abramis bjoerkna, Abramis ballerus, Lota lota, Gymnocephalus cernuus, Sander lucioperca), but there are some adventive ones (Pseudorasbora parva, Carassius gibelio, Ameiurus melas, Lepomis gibbosus, Perccottus glenii) and a spontaneously immigrated species as well (Proterorhinus marmoratus). Specific natural values of the watershed are the isolated population of minnow (Phoxinus phoxinus) in Kulcsárvölgyi Brook and the frequently occurring mudminnow (Umbra krameri) in the lower reach of Hejő Brook.